Moral Education in Islamic Boarding Schools for Shaping the Social Character of Adolescents - Astuti, Livia; Winarti, Agus (LETIGES, 2026)
This study stems from the growing phenomenon of declining politeness among adolescents, a lack of empathy, weak social responsibility, and a deterioration of moral attitudes. It seeks to explore how moral education provided in Islamic boarding schools influences students' ability to socialise and interact within the community. This study focuses on moral education in Islamic boarding schools in shaping the social character of adolescents at Nahrul Ulum Al Banihawy Islamic boarding school, Subang Regency, West Java, Indonesia. The purpose of this study is to describe how moral education in Islamic boarding schools contributes to the development of adolescents' social character within society. Moral education in Islamic boarding schools not only shapes adolescents' character but also involves the process of habituating students' behaviour. This study employs a qualitative research method using a phenomenological approach, aiming to explore the phenomenon deeply and naturally. Data collection techniques include open interviews, observation, and documentation. The interviews were conducted with the administrators (kyai), teachers (ustadz/ustadzah), and students (santri). Observations were carried out on all 40 students, ranging in age from 13 to 20 years old. Documentation was conducted throughout the research process. The results of the study indicate that the formation of social character is carried out through three main indicators: 1) the personal dimension emphasises the habituation of honest, disciplined, and responsible behavior through routine activities; 2) the social dimension is reflected in attitudes of empathy, cooperation, and concern for others; and 3) the spiritual dimension is developed through the practice of worship, the study of classical Islamic texts (kitab kuning), dzikr, and other religious activities that foster students closeness to Allah Swt. These three indicators are implemented through exemplary behaviour, habituation, and discipline. The originality of this study lies in its unique context, focusing on a newly established Islamic boarding school with only 40 students and one graduating cohort. This setting provides an authentic view of the early stages of character and social skills formation in a developing Islamic Boarding Schools environment.